Rivulus sape, a new species of killifish (Cyprinodontiformes: Rivulidae) from the Paragua River system, Caroní River drainage, Guyana Shield, Venezuela - Lasso-Alcalá, Oscar M.; B., Donald C. Taphorn; Lasso, Carlos A.; León-Mata, Oscar (Zootaxa, 2006)
A new species, Rivulus sape, is described from two tributaries of the upper Paragua River, Caroní River drainage, of the Guyana Shield in Venezuela. It is a small (all specimens examined less than 50 mm SL), apparently non-annual species that is distinguished from congeners in having the dorsal, anal, and pelvic fins short; adult males with a truncate caudal fin with the upper and lower borders black; and an iridescent blue, ovate spot on sides of the body above the pectoral fins. Neither adults nor juveniles have an ocellus at the dorsal junction of the caudal peduncle and caudal fin. Only one contact organ per scale on some scales along the sides of the body was observed.